Discovery of potential DNA methylation markers for forensic tissue identification using bisulphite pyrosequencing. Issue 21 (27th September 2016) - Vidaki, Athina; Giangasparo, Federica; Syndercombe Court, Denise
Abstract : The presence of specific body fluids at crime scenes could be linked with particular types of crime, therefore attributing a DNA profile to a specific tissue could increase the evidential significance of a match with a suspect. Current methodologies such as tissue‐specific mRNA profiling are useful but drawbacks include low tissue specificity and applicability to degraded samples. In this study, the potential of 11 tissue‐specific differentially methylated regions, initially identified following large‐scale methylation analysis of whole blood, buccal cells and sperm, was explored in order to identify markers for blood, saliva and semen. Bisulphite pyrosequencing analysis supported previous findings, but tissue‐specific differentially methylated regions for blood and buccal cells did not show enough specificity to be proposed as markers for blood and saliva, respectively. For some CpGs, a large inter‐individual variation in methylation levels was also observed. Two of the semen markers (cg04382920 and cg11768416) were used for further validation on a large set of stains. These two semen‐specific assays showed high sensitivity (as low as 50 pg) and stability. Future experiments will shed light on the usefulness of these markers in forensic casework.